Rubisco content and CO2 assimilation activity in flag leaf during ontogeny in winter wheat varieties of different productivities - Frantiychuk, V. V.; Sitnik, S. K.; Stasik, O. O.; Mikhno, A. I. (Reports of the National Academy of Sciences of Ukraine, 2016)
It is established that the rubisco content in flag leaf of winter wheat plants closely positively correlates with the photosynthesis activity during grain ripening and senescence of the photosynthetic apparatus. Maintaining a high rubisco level and CO2 assimilation at later stages of reproductive development depend mainly on genetically determined stay-green traits of the variety and are improved with increasing the mineral nutrition. The maximum accumulation of rubisco in young flag leaf of wheat plants at anthesis is related rather to the nitrogen deposition and does not correlate with the intensity of photosynthesis.